Estudo de caso sobre as ações indenizatórias provenientes de acidentes de trânsito na segunda vara cível de Gurupi/TO - Silva, Nilson Afonso da (Universidade Federal do Tocantins, 2016)
Living in society is extremely complex, requiring from time to time checking how institutions established act to fulfill their constitutional duties and whether jurisdiction can be effective in strict adherence to human rights. It’s necessary to point out that human rights do not deserve a narrow view, in the sense that they are aimed at defending those who commit crime - as many people believe. The Human Rights are intended to guarantee to all, without distinction, compliance with the constitutional provisions, especially the human dignity and the fundamental rights. If the laws in effect are met, a priori human rights will also be respected. To this end, it is necessary the analysis of data collected scientifically to be known how the state agency (Judiciary) responsible for the jurisdictional service of results is considering the constitutional text. By being invested of part of the State power, it is assumed that it is working according to constitutional principles, doing everything necessary so that social peace is restored. It must be checked if the judiciary is doing its duty and prerogatives and if the process has a rite that allows its duration within a reasonable time. And in the case of origin of the requests, can the judiciary deliver the good of life sought, ie, give efficiency and effectiveness considering the process use? Was there victim compensation proportionate to the damage suffered and in reasonable time in order to minimize and compensate their suffering? Surely that the research should be more comprehensive, what happens is that, due to material difficulties, there is no way to add to the work other researchers, noting that the surveys were conducted only by this master student under the Second Civil Court of the Gurupi County together with the military police of Tocantins State (4th BPM). The Map of Violence of 2013, released by the Ministry of Health, shows that, proportionally, Tocantins is in first place in the rise in the number of people who die in traffic. In the survey, which brings numbers from 2001-2011 there are 37.9 deaths per 100,000 inhabitants in the state. In 2011, there were 531 traffic deaths, representing 64.9% compared to 2001 when 322 deaths were recorded. The irresponsible behavior in traffic, especially of driving under the influence of alcohol or other drugs, is a constant concern of the authorities. In 2011, the United Nations proclaimed the Decade of Action for Safety in Traffic and issued a challenge to the countries: halving the number of traffic deaths in a period of 10 years. Therefore, we investigate the judgments in suits for damages from traffic accident in Gurupi County, specifically in the Second Civil Court, from September 2012 (the beginning of the electronic process in the County) until September 2015, responding to end which was the deadline for the effective adjudication, and what would be a reasonable time of the procedure for these specific actions. At the end, confirming the failure to comply with the principle, it is pointed out possible proposals for solutions to the delay. Inductively, the data raised in legal proceedings were analized, the Military Police data from Gurupi / TO, research available in the CNJ and Seguradora Líder (DPVAT) and literature on the subject.